Analisis Pengaruh Respon Kontrol Posisi Motor dan Beban terhadap Nilai Arus serta Tegangan pada Kontroler Motor BLDC - Rendi Setiawan Norardi; Fatkhur Rohman Rohman (Universitas Merdeka Malang, 2020)
The use of BLDC motors is currently on the rise, especially in Indonesia. The advantages are the high efficiency of the asynchronous motor, the small size of the electronics, the sensor and the control system. One obstacle to the use of BLDC motors is that the BLDC motor control system is still underdeveloped. The controller becomes the main system for starting the BLDC motor. In addition, the controller requires a security system to prevent damage. The purpose of this study is to analyze and study the current and voltage safety system on the controller to minimize damage. The data collection method in this study was to sample the highest current and voltage values in each position control on the Odrive controller and load changes on the prototype electric vehicle. The results of a study with a Dys2826 1400 kV DC induction motor showed no significant effect of position control variations on current and voltage at a distance of 1 to 5 meters. In this case, a change in load affects the values of current and voltage at a load of 1 to 5 kilograms. This is because the motor needs a lot of current to maintain position in position control mode.